Evidence demonstrating the pharmacist's direct impact on clinical outcomes in pediatric patients: An opinion of the pediatrics practice and research network of the American College of Clinical Pharmacy. Issue 4 (6th April 2020) - LaRochelle, Joseph M.; Smith, Katherine P.; Benavides, Sandra; Bobo, Kelly; Chung, Allison M.; Farrington, Elizabeth; Kennedy, Audrey; Knoppert, David; Lee, Bernard; Manasco, Kalen B.; Pettit, Rebecca; Phan, Hanna; et al.
Abstract: The pharmacist's role in pediatric care is critical for the provision of safe medication use secondary to differences in physical development, frequent off label use of medications, need for dose calculations, and the lack of standard dosage forms. Many regulatory agencies, health care organizations, and professional societies support the pharmacist as a member of the interdisciplinary team. However, specific details showcasing how pharmacists impact the care of pediatric patients in a quantifiable and meaningful way have not been well described. The purpose of this article is to provide a review of evidence demonstrating measurable clinical outcomes directly resulting from pharmacist participation in pediatric patient care. This report is an opinion paper of The American College of Clinical Pharmacy (ACCP) Pediatrics Practice and Research Network and has been endorsed by the Pediatric Pharmacy Association (PPA). This article represents the opinion of the Pediatrics Practice and Research Network of ACCP. It does not necessarily represent an official ACCP commentary, guideline, or statement of policy or position.